2016
DOI: 10.1556/018.67.2016.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential oil combinations on pathogenic yeasts and moulds

Abstract: Essential oils (EOs) can be used as alternative or complementary antifungal agents against human pathogenic moulds and yeasts. To reduce the effective dose of antimicrobial agents, EOs are combined which can lead to synergistic or additive effect. In this study the anti-yeast and anti-mould activities of selected EOs were investigated, alone and in combinations, against clinical isolates of Candida albicans, C. parapsilosis, Aspergillus fumigatus, A. terreus, Rhizopus microsporus, Fusarium solani and Lichtheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…This difference between MIC and MFC has been reported by several authors on different Fusarium species [27][28][29] and other mold species [15,17].…”
Section: Determination Of Mic In Agar Medium and Mic And Mfc In Liquisupporting
confidence: 48%
“…This difference between MIC and MFC has been reported by several authors on different Fusarium species [27][28][29] and other mold species [15,17].…”
Section: Determination Of Mic In Agar Medium and Mic And Mfc In Liquisupporting
confidence: 48%
“…Several studies have shown that clove and cinnamon oils had a strong and inhibitory activity against different Candida species (Aneja & Joshi, 2010;Fani &Kohanteb, 2011 andRadwan et al, 2014). In the same situation, the combination cinnamon with clove oils leading to enhancement of the antifungal activity in all cases (Horváth et al, 2016). Omran & Esmailzadeh (2009) indicated that lemon essential oil has a low inhibited effect on different Candida species.…”
Section: Discussionmentioning
confidence: 99%
“…Citrus aurantifolia Limão Tahiti Geranial, limoneno e β-pineno (Chao et al, 2000) Cymbopogon martinii Palmarosa Acetato de geranil e geraniol (Chao et al, 2000) Cymbopogon winterianus Citronela Citronelal, citronelol e geraniol (Horváth et al, 2016) Eugenia caryophyllus Cravo Eugenol e β-cariofileno (Horváth et al, 2016) Eugenia caryophyllus (folha) Cravo folha Eugenol e β-cariofileno (Horváth et al, 2016) Litsea cubeba Pimenta chinesa, May Chang Sabineno, 1,8cineol, α-pineno e βpineno (Thielmann and Muranyi, 2019) Mentha arvensis Hortelã Menthol e p-menthone (Pandey et al, 2003) Mentha piperita Hortelã-pimenta Sabineno, limoneno, α-pineno e β-pineno e β-cariofileno (Chao et al, 2000) Ocimum basilicum Manjericão Metilchavicol (Císarová et al, 2016) Origanum vulgare Orégano Carvacrol (Císarová et al, 2016) Piper nigrum Pimenta preta Sabineno, limoneno, α-pineno e β-pineno e β-cariofileno (Chao et al, 2000) Thymus vulgaris Tomilho Timol, p-Cymene e 1,8cineol (Horváth et al, 2016) Zingiber officinale Gengibre Canfeno, neral, geranial + acetato de bornila (Chao et al, 2000) Fonte: Autores.…”
Section: Nome Científico Nome Popular Composto Majoritáriosmentioning
confidence: 99%
“…Portanto, apesar do acentuado efeito inibitório, provocando um grande retardo no início do crescimento micelial do patógeno, pode ser que a utilização desses compostos possa ser bastante limitada, em função dessas possibilidades. Os óleos essenciais apresentam, geralmente, um amplo espectro de ação, proporcionando a inibição ou morte dos mais distintos gêneros de fungos e bactérias (Bakkali et al, 2008;Gogoi et al, 1997;Horváth et al, 2016;Lee et al, 2020;Sharma et al, 2017;Thielmann and Muranyi, 2019). Isso significa que estruturas comuns a todas as espécies, como, por exemplo, a membrana plasmática, sejam afetadas, ou estruturas comuns a determinados grupos de microrganismos, como a membrana mitocondrial em eucariotos ou a bomba de prótons em procariotos (Bakkali et al, 2008).…”
Section: Teste In Vitro Dos óLeos Essenciais Na Concentração De 01%unclassified
See 1 more Smart Citation